Konseling Lintas Budaya dan Agama (Nilai-Nilai pada Masyarakat Suku Batak dalam Melakukan Pendampingan terhadap Disabilitas) - Merryanne Elisabet Sinaga; Yurulina Gulo (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2020)
This study aims to describe and analyze the values of life that "disability" occurs not because of a curse so that it experiences "disability." Through the use of social values in the Batak Tribe, acceptance and support for people with disabilities can build good relations. This research uses a qualitative-descriptive approach. Data was obtained through in-depth interviews from the municipal government and Central Tapanuli Sibolga District, religious leaders, elements of the Hepata Laguboti Panti Karya community institution and Sibolga RBM as sources and direct interviews with Disability families. The process of community social counseling occurs because of differences through perspective, mindset, and culture in reality. The counseling action towards the counselor is carried out through acceptance, respect and respect in accordance with the cultural elements in the existing community. Through Cross-Cultural and Religious Counseling it is necessary to provide assistance to Disability Welfare, especially for Bataks, where there is still an understanding that "Disability" is caused by curses. Through cross-cultural and religious counseling, Batak tribal values are used to humanize humans, because humanizing humans is part of justice in society